2017
DOI: 10.1007/s12031-017-0942-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of Apolipoproteins and α-Synuclein in Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a progressive brain disorder that interferes with activities of normal life. The main pathological feature of this disease is the loss of more than 80% of dopamine-producing neurons in the substantia nigra (SN). Dopaminergic neuronal cell death occurs when intraneuronal, insoluble, aggregated proteins start to form Lewy bodies (LBs), the most important component of which is a protein called α-synuclein (α-syn). α-Syn structurally contains hexameric repeats of 11 amino acids, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 121 publications
0
27
0
Order By: Relevance
“…However, it is unclear how alterations of the SNCA gene cause Parkinson disease. More recently, plasma and CSFα -synuclein has been shown to be associated with cognitive decline in PD (Emamzadeh, 2017 ) and as a potential biomarker of cognitive decline in PD.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is unclear how alterations of the SNCA gene cause Parkinson disease. More recently, plasma and CSFα -synuclein has been shown to be associated with cognitive decline in PD (Emamzadeh, 2017 ) and as a potential biomarker of cognitive decline in PD.…”
Section: Introductionmentioning
confidence: 99%
“…They have been linked to neurodegenerative disorders including Alzheimer disease, including in our recent proteomic study of CSF [54]. APOE variants were shown to exhibit neuroprotective activity (reviewed in [65]). APOA1 is the major protein component of plasma high-density lipoprotein and its low levels in CSF and plasma have been reported as a potential PD biomarker [66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…Apolipoprotein E is the most abundant apolipoprotein in the central nervous system, and its secretion by astrocytes is responsible for neuronal cholesterol homeostasis, neuronal growth, membrane plasticity, and synapse development (Emamzadeh, 2017). Recent studies have revealed that ApoE is associated with cognitive decline but not the development of PD (Peplonska et al, 2013;Multhammer et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Apolipoprotein E isoforms are associated with Aβ plaque deposition ( Irwin et al, 2013 ; Paul et al, 2016 ) and α-synuclein aggregation ( Emamzadeh et al, 2016 ; Emamzadeh, 2017 ) in PD, with ε4 considered to carry a higher risk than either of the others (ε2 and ε3). Paul et al (2016) and Tropea et al (2018) examined associations between genes and PD susceptibility and found that ε4 carriers exhibit faster decline than non-carriers in many neuropsychological test scores.…”
Section: Discussionmentioning
confidence: 99%